Choroidal Melanoma: Our Experience - Hamal, Diwa; Limbu, Ben; Sthapit, Purnima Rajkarnikar; Pradhan, Eli; Shrestha, Reshmi; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2019)
Background: Choroidal melanomas are diagnosed in approximately 6 out of one million Americans per year, and although their incidence is low, they are the most common primary intraocular tumor in adults. Methods: Choroidal melanoma is rare tumors and till date no such reports with sclera involvement has been reported from Nepal. It is a prospective case series. The aim of this study is for awareness of the severity of the Choroidal melanoma and it’s management. Besides, it is also to study the demography, presentation, histopathological variations and management of cases of choroidal melanoma. All the consecutive cases of Choroidal melanoma presenting between Jan 2017 to May 2018 and those who were within the inclusion criteria were included in this study. Results: There were eight patients, five male and three female, within age range of 18-73, median age was 47. All patients presented with decreased vision ranging from 6/24 to PL of less then three months to 2 years duration. Fund us showed choroidal mass associated with Vitreous hemorrhage (VH), and retinal detachment (RD). Two patients were managed with enucleation with External beam radiotherapy (EBRT). Four underwent only enucleation. One patient with lesion size less then 10mm under went plaque brachy therapy. One patient underwent initially Plaque brachy therapy but later had to undergo Enucleation. Histopathological examination (HPE) of enucleated patient revealed epitheloid cell melanoma grade three in four and Spindle cell melanoma in three patients. Each one patient of epitheloid cell melanoma and spindle cell melanomahad scleral involvement. Indication for radiotherapy was scleral involvement. Conclusion: With 8 cases of Choroidal melanoma in a single year in a single hospitalgives us a clue that there may be much more undiagnosed cases of Choroidal melanomain Nepal that should be taken seriously. Going for annual eye examination with routine dilated fund us exams can help in prevention and early diagnosis of this life and sight threatening condition and to reduce the mortality rate.